Figure and Scope of Ideas of Ludwig Wittgenstein in W.G. Sebald’s Austerlitz - Elizaveta V. Sokolova (Studia Litterarum)
The article examines the multilevel influence of the personality and ideas of Ludwig Wittgenstein (1889–1951) on the literary text of the significant German writer (and academic literary researcher) of the 1990s W.G. Sebald (1944–2001) — first of all, on the example of his final work, the novel Austerlitz (2001), in which the most important themes and main stylistic and artistic strategies of the writer culminate. It is shown that the features of this text, including ways and patterns of movement and unfolding of thought in it, reflect and echo Wittgenstein’s ideas on “family resemblance” as a hidden principle organizing human language and experience (Philosophical Investigations, 1953). Since the research methodologically relies on a systematic approach, within which the writer’s creative heritage is viewed as a unity with its own hierarchy, structure, network of internal and external correspondences, an assumption is made, confirmed by several examples from other writer’s texts, that the identified functions and ways of existence of L. Wittgenstein’s image and ideas are characteristic for the literary text of the writer as a whole.